TANGGUNG JAWAB NEGARA TERHADAP JAMINAN PELAYANAN KESEHATAN DALAM PERSPEKTIF HAK ASASI MANUSIA - Mardhatillah, Wulan; Firdaus, Emilda; Deliana, Evi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Law Number 36 of 2009 concerning health indicates that every individual,family and community has the right to obtain protection for their health, and thestate is responsible for regulating the fulfillment of the right to live healthily forits inhabitants including for the poor who cannot afford it. Efforts to realize thisright, the government must provide health services that are equitable, fair andaffordable for all levels of society. For this reason, the government needs to makeefforts to ensure equitable access for all citizens to obtain health services. Article52 of the Presidential Decree paragraph (1) letter r excludes the public fromreceiving health services due to criminal acts of persecution, sexual violence,victims of terrorism, and criminal acts of trafficking in persons.This research will be compiled using the juridical normative type ofresearch, which is research that is focused on examining the application of normsin positive law. The approach used in this research is to use a normativeapproach, namely literature law research.The results of the research conducted by the author are, first to find outhow legal protection and state responsibility in the context of protecting humanrights and to get the right to health services for the community is part of theimplementation of protection of human rights, then to know the legal ideas onhealth rights. Citizens have the right to guarantee good health services, andprioritize the safety or life of patients without first paying attention to the causeand effect of why the victim becomes sick, and presidential regulations or othergovernment regulations do not make an exception to which victims have the rightto be accepted when they want to seek treatment.Keywords: State Responsibility - Health Services